Analysis of Transportation Mode Choice to Campus by Students of Pahlawan University - Firmansyah, Andries; Adeswastoto, Hanantatur; Fiatno, Aris (Journal of Engineering Science and Technology Management, 2026)
Transportation is an essential element in daily life, especially for students with high mobility. This study aims to analyze the choice of transportation modes used by Pahlawan University students on their way to campus. This study highlights student characteristics, factors influencing mode choice, and modeling of transportation mode choice. The method used is a quantitative approach through the distribution of online questionnaires to 100 active student respondents in the 2024–2025 academic year. Data were analyzed using descriptive analysis and binary logistic regression with the help of SPSS software. The results show that the most commonly used mode of transportation is private vehicles, especially motorcycles. The study found that 'pocket money' (allowance) is a significant factor influencing transportation mode choice. The binary logistic regression model provides a robust statistical picture of student mode preferences in the local context of Bangkinang. This research is expected to serve as a reference in making transportation policies on campus and provide input for the development of an efficient transportation system that meets student needs.